Gojek Driver Partners in Banjarmasin: Factor Affecting Tax Compliance with Tax Sanctions as a Moderation Variable - Nastiti, Rizky; Syahdan, Saifhul Anuar; Fauzi, Cherrya Chairunnisa Maulidya; Ruwanti, Gemi; Asiah, Antung Noor (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2023)
This study aims to empirically test and analyze the effect of tax awarness, tax knowledge and tax morale on tax compliance and the interaction variables between tax awareness, tax knowledge and tax morale with tax penalty of Gojek driver partners in the city of Banjarmasin. Moderation variable on this study is Tax Penalty. This study uses secondary data with a sample of 157 Gojek partners in Banjarmasin using a random sampling method. The data then analyzed by using multiple regression analysis model and Moderated Regression Analysis (MRA). The results of this study indicated that tax awareness and tax knowledge had a significant effect on tax compliance. However, ttax morale had no significant effect on tax compliance. In addition, tax penalty could not moderate the relationship between tax awareness and tax knowledge with tax compliance. However, it can moderate tax morale relationship with tax compliance.